PENGARUH MODEL PEMBELAJARAN PENDEKATAN TAKTIS DAN MODEL PEMBELAJARAN PENDEKATAN TRADISIONAL TERHADAP MOTIVASI, KETERAMPILAN BERMAIN DAN KETERAMPILAN TEKNIK DASAR DALAM BERMAIN BOLABASKET - Stephani, Mesa Rahmi (STKIP Pasundan, 2016)
This research is based on facts in the field regarding the current learning conditions of Physical Education, which have been reviewed in several forums by several observers of physical education. The learning methods used by many teachers tend to be traditional. The learning model used is still centered on the teacher (Teacher Centered), where students perform basic technical skills in a sport. This study aims to determine which learning models are good in Physical Education learning in schools. The independent variable in this study uses the Tactical Approach Learning Model and Traditional Approach. Dependent variables in this study are motivation, play skills and basic technical skills in basketball. The research method uses quantitative research methods with one group pre-post test design design, using experimental treatment of the sample. The sampling technique in this study uses random sampling with the return of samples to the population, because the population is large. The sample consisted of 80 people, each treatment group totaling 40 people. Data analysis in this study used multivariate data analysis using the SPSS program. The results of this study include: (1) There is no difference in motivation in playing basketball between the tactical approach learning model and the traditional approach learning model. (2) There are significant differences in basketball playing skills between the tactical approach learning model and the traditional approach learning model. (3) There are significant differences in basic technical skills in basketball between the tactical approach learning model and the traditional approach learning model.